Narrative Review: Pathogenesis and Management Of Diabetic Retinopathy - Febriansyah, Febriansyah; Marlyanti Nur Rahmah; Muhammad Jabal Nur; Pratiwi Nasir Hamzah; Sri Irmandha Kusumawardhani (Jurnal EduHealth, 2024)
Diabetic Retinopathy is a microvascular disorder that occurs due to the long-term effects of diabetes mellitus. Diabetes mellitus (DM) is caused by metabolic disorders that occur in the pancreas organ which is characterized by increased blood sugar or often referred to as hyperglycemia which is caused by a decrease in the amount of insulin from the pancreas. This can cause damage to the retina that threatens vision and can cause blindness. Effective management requires a multidisciplinary approach that includes glucose control, medical intervention, and patient education. This study aims to determine the pathogenesis and management of Diabetic Retinopathy. This research is a literature study with a narrative review approach. The literature reviewed is literature obtained from databases that have been accredited or indexed by Sinta. The results of this literature study show that vascular dysfunction including loss of pericyte cells, formation of acellular capillaries (endothelial cell death), thickening of the basement membrane and increased capillary permeability to the closure of blood vessels leading to retinal ischemia-infarction is the pathogenesis of diabetic retinopathy. Management of diabetic retinopathy depends on the severity of the symptoms. Treatment does not only consist of observing blood sugar control, systemic hypertension and hypercholesterolemia, but also therapy such as laser photocoagulation, administration of Anti-Vascular Endothelial Growth Factor (Anti-VEGF), intravitreous steroids or IVTA (Intra Vitreous Triamcinolone Acetonide), and other procedures. pars plana virectomy.